The effects of minocycline on spinal root avulsion injury in rodent model : a histological study - Yew Chin, Tan (2015)
Introduction: Brachial plexus injuries are debilitating injury affecting young population, which comprise 5 % of all polytraumas caused by road traffic accidents. Currently the primary aim for the management of root avulsion of the brachial plexus is motor recovery. However, immediate repair or nerve grafting offers some degree of protection to the motoneurons but is clinically limited, so there remains a need for medical approaches to maintain the viability of the injured motor neurons. Minocycline has been proven to show its neuroprotective effect in stroke and demyelination disease. It is a widely available, cost effective antibiotic with anti-inflammatory and anti-apoptotic properties. Literatures have shown that Minocycline exert its neuronal protection effect primarily via Migroglial inhibition and Nitric Oxide Synthase downregulation. Both of the effects are key therapeutic means to ameliorate neuroinflammatory and degenerative process following secondary traumatic avulsion injury. Objective: To study the Neuroprotective effect of Minocycline in adult Sprague Dawley mouse that suffer from Brachial Plexus Injury. Methods: The C7 nerve root was avulsed via anterior extravertebral approach. The traction force transected the ventral motor nerve roots at the preganglionic level. The avulsed rootles can be seen under the microscope for validation of the avulsion rodent model in which the avulsion is properly done at the preganglionic level. The rodents in which the transection takes place distal to the rootlets were excluded from the study Intraperitoneal and intrathecal Minocycline 50mg/kg for the first week and (25mg/kg for the seconda week) was administered to promote motor healing. The spinal cord was harvested at 6 weeks after the injury to analyze the structural changes following avulsion injury and the pharmacological intervention. Results: Motor neuron death and microglial proliferation was observed following traumatic avulsion injury of the ventral nerve root. The administration of Minocycline to treat rodents suffering from avulsion injury was capable to suppress the Microglial proliferation. Intraperitoneal administration of Minocycline shows some degree of beneficial effect to prolong the motor neuron survival by inhibiting the Microglia activation and proliferation, thus hampering apoptosis of the motor neuron. However when Minocycline was administered via intrathecal route to increase the bioavailability of the therapeutic agent, not only that it compromises the motor neuron survival, some other deleterious effect were also demonstrated. Conclusion: Microglial suppression via Minocycline can have double effect. Moderate dosage of Minocycline may be beneficial towards motor neuron survival. On the other hand, high concentration of Minocycline ( similar drug dosage with increased potency via targeted drug delivery) could be neurotoxic by causing impairment of the Glial response and Wallerian degeneration, which is a pre-requisite to regeneration.